Marketing Communication Strategy for Building Graha Padjadjaran Developer’s Corporate Image in Depok - Naufal Nur A’lam; Sa’diyah El Adawiyah (Politeknik Siber Cerdika Internasional, 2026)
Background: In the competitive property market of Depok City, effective marketing communication is a critical strategy for developers seeking to build a positive corporate image. Service quality and product quality play essential roles in ensuring consumer satisfaction, minimizing complaints, and sustaining the company's reputation. Objective: This study aims to examine how Graha Padjadjaran Developer implements marketing communication strategies to build its corporate image and to explain the contribution of each marketing communication dimension in shaping that image. Methods: Grounded in Kotler and Keller's Integrated Marketing Communications (IMC) theory — encompassing promotion, advertising, personal selling, direct marketing, and public relations — this research employs a qualitative case study with a descriptive design. Data were collected through observation, in-depth interviews with marketing staff, sales personnel, and consumers, and documentation of online marketing materials. Results: Graha Padjadjaran's marketing communication centers on providing clear product information, employing emotional consumer engagement, and maintaining intensive follow-up communication to build trust. Meta Ads platforms (Instagram Ads and Facebook Ads) serve as the primary digital marketing channels. Each IMC dimension contributes distinctly to image formation: promotion expands market awareness, advertising conveys credibility through visual content, personal selling positions the marketing team as the company's frontline representatives, and direct marketing fosters long-term consumer relationships through personalized service. Conclusion: This study concludes that integrated marketing communication strategies — promotion, advertising, personal selling, direct marketing, and public relations — significantly strengthen Graha Padjadjaran's corporate image, while effective complaint handling through service excellence reinforces sustained consumer trust.